Allusive Gestures in Book “Ghar-E-Hira Main Aik Rat” by Mustansar Hussain Tarar - Bano, Ruqia; Mehboob, Sabrina; Niaz, Minhaj (sourcecoder, 2025)
Mustansir Hussain Tarar was born in Lahore. He belonged to the Merchant Family. Mustansir Hussain Tarar’s status is like a school of thought in Urdu Literature because his services in Urdu literature are as novelist, fiction writer, dramatist and travel writer. He has also shown the essence of his acting on T.V. As a reward for his services, he has also been awarded the presidential award for best performance by the government of Pakistan. In this research the use of Allusive Gesture has been brought out which he has used as sign in his book.